Sevoflurane Induces Exaggerated and Persistent Cognitive Decline in a Type II Diabetic Rat Model by Aggregating Hippocampal Inflammation - Li, Dongliang; Liu, Lingling; Li, Liang; Li, Xingang; Huang, Bin; Zhou, Changqing; Zhang, Zhaohang; Wang, Chunling; Dong, Ping; Zhang, Xiyan; Yang, Bo; Zhang, Li (Frontiers in Pharmacology, 2017)
Recent studies show that a moderate duration of sevoflurane, one of the most commonly used volatile anesthetics in clinical practice, does not induce cognitive impairment in animals under physiological conditions. However, the influence of sevoflurane on cognitive function under diabetic conditions remains unclear. The aim of this study was to determine whether sevoflurane causes cognitive decline in a rat model of type 2 diabetes mellitus (DM) and if so, to explore a possible underlying mechanism. Diabetic Goto–Kakizaki (GK) rats and non-diabetic Wistar rats underwent 2.6 % sevoflurane for 4 hours or sham (control) exposure. Cognitive function and hippocampal inflammation were assessed 1 week and 5 months after sevoflurane or sham exposure. Compared with Wistar control rats, GK control rats exhibited shorter freezing times in Trace fear conditioning task 1 week after exposure, took longer to locate the submerged platform and had shorter dwell-time in the target quadrant in Morris Water Maze task 5 months after exposure. GK rats that received sevoflurane not only exhibited less freezing times 1 week after exposure, but also spent more time to locate the submerged platform and had less dwell-time in the target quadrant, compared with GK control rats. Molecular studies revealed that the levels of pro-inflammatory cytokines and activated microglia in the hippocampus were higher in GK control rats than those in Wistar control rats at both time points and were further increased in GK rats receiving sevoflurane. Wistar rats that received sevoflurane and Wistar control rats did not differ in any cognitive performance and molecular assessment. The results suggest that diabetic GK rats exhibit cognitive dysfunction probably due to increased hippocampal inflammation, and that sevoflurane induces exaggerated and persistent cognitive decline in GK rat by aggregating hippocampal inflammation.